2021
DOI: 10.3390/su13115966
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements in Cognitive Performance and Academic Achievement in Adolescents through the Hybridization of an Instructional Model with Gamification in Physical Education

Abstract: An educational physical education (PE) hybridization program based on the personal and social responsibility model and gamification strategies was used in order to explore the effect on cognitive performance and academic achievement. A 9-month group-randomized controlled trial was conducted, with 150 participants (age: 14.63 ± 1.38) allocated into the control group (CG, n = 37) and experimental group (EG, n = 113). Inhibition, verbal fluency, planning, and academic achievement were assessed. Significant differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…The authors highlight, as the main finding, the prevalence of the transfer of autonomy and responsibility in the teacher's behaviors to the participants, which generated a more self-determined motivation among the students, thus improving the levels of autonomy, responsibility and motivation. In a similar study by Melero-Cañas [41] with the hybridization of the social and personal responsibility model and gamification, it was confirmed that the gamified hybrid intervention produced improvements in cardiorespiratory fitness, agility and speed-agility, in addition to reducing the time of sedentary lifestyle during the week and weekend. The students in the control group obtained a greater increase in Body Mass Index.…”
Section: Gamification In Physical Education In Middle Junior and High...mentioning
confidence: 68%
“…The authors highlight, as the main finding, the prevalence of the transfer of autonomy and responsibility in the teacher's behaviors to the participants, which generated a more self-determined motivation among the students, thus improving the levels of autonomy, responsibility and motivation. In a similar study by Melero-Cañas [41] with the hybridization of the social and personal responsibility model and gamification, it was confirmed that the gamified hybrid intervention produced improvements in cardiorespiratory fitness, agility and speed-agility, in addition to reducing the time of sedentary lifestyle during the week and weekend. The students in the control group obtained a greater increase in Body Mass Index.…”
Section: Gamification In Physical Education In Middle Junior and High...mentioning
confidence: 68%
“…From the 15 selected papers, mostly were experimental research as illustrated in Fig. 2, namely 73% or 11 articles (Cañabate et al, 2020;Kolovelonis et al, 2023;Koszałka-Silska et al, 2021;Luna et al, 2021;Meijer et al, 2022;Melero-Cañas et al, 2021;Mullender-Wijnsma et al, 2019;Pirrie & Lodewyk, 2012;Wawrzyniak et al, 2022), followed by correlational 13% or 2 articles (Gwon & Shin, 2023;Morita et al, 2016), explanatory 7% or 2 articles (Jeon et al, 2021;Rillo-Albert et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Interventional program is also varied between studies. However, Melero-Cañas et al (2021) and Wawrzyniak et al, (2022) argue that in order to yield significant effect especially on cognitive and psychomotor domain, intervention should be done through whole academic year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations